PENGARUH SOCIAL MEDIA MARKETING DAN INFLUENCER CREDIBILITY TERHADAP PURCHASE INTENTION MELALUI BRAND TRUST - Delvina Carissa; Rodhiah (ITB AAS Indonesia Surakarta, 2025)
The skincare industry is currently facing very tight competition, especially with the emergence of various local and international brands. This research aims to analyze the influence of social media marketing and influencer credibility on purchase intentions with brand trust as a mediating variable. The population of this research is all Indonesian people who live in the Jabodetabek area and know the S brand. This research uses purposive sampling as a sampling technique with sample criteria, namely people living in the Jabodetabek area aged 19 years and over who know skincare products from the S brand, and know TF as an influencer from the X brand. Data was collected from 204 respondents through distributing questionnaires online using Google Form media. Data were analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.0 software. The research results show that social media marketing has a significant and positive effect on purchase intention. Brand trust also has a significant and positive influence on purchase intention. In addition, the data shows that influencer credibility has a significant and positive effect on purchase intention. Brand trust is proven to mediate the influence of social media marketing on purchase intention. The data results show that brand trust has the strongest influence on purchase intention. Keywords: Social Media Marketing, Influencer Credibility, Brand Trust, Purchase Intention